Glass fiber and nanoclay reinforced polypropylene composites: morphological, thermal and mechanical properties - Normasmira A. Rahman,; Aziz Hassan,; Yahya, R.; Lafia-Araga, R.A. (Universiti Kebangsaan Malaysia, 2013)
Hybrid composites of polypropylene (PP)/nanoclay (NC)/glass fiber (GF) were prepared by extrusion and injection molding. Molded specimens were analyzed by transmission electron microscopy (TEM), thermogravimetric analysis (TGA), tensile and flexural tests. TEM results revealed NC particle intercalation. TGA results showed that the incorporation of clay into the GF composite improves the thermal stability of the material. The initial thermal decomposition temperatures also shifted to higher values. Incorporation of GF into PP lowers the tensile strength of the binary composite, indicating poor fiber-matrix interfacial adhesion. However, introducing NC increased the strength of the ternary composites. Tensile modulus was enhanced with the incorporation of GF and further increased with an introduction of NC. Flexural strength and flexural modulus are both enhanced with an increase in GF and NC loading.